Aspects of violence in Renaissance Europe - Davies, Jonathan; Davies, Jonathan (Ashgate, 2013)
1. Interpersonal and Ritual Violence -- Student Violence in Fifteenth-Century Paris and Oxford / Hannah Skoda -- The Politics of Transition : Pillaging and the 1527 Sack of Rome / Joëlle Rollo-Koster -- Death on the Danube / Miriam Hall Kirch -- Plague, Propaganda and Prophetic Violence in Sixteenth-Century Lyon / Justine Semmens -- 2. War -- Rethinking the Peace of Westphalia : Toward a Theory of Early Modern Warfare / Alan James -- "Broken Verses across a Bloodied Land" : Violence and the Limits of Language in the English Civil War / Sarah Covington -- Peter Paul Rubens : Broker of Peace, Painter of Violence / Marina Daiman -- 3. Justice -- Violence, Rites, and Social Regulation in the Venetian Terra Firma in the Sixteenth Century / Lucien Faggion -- "Una causa civile" : Vendetta Violence and Governing Elites in Early Modern Modena / Amanda G. Madden